Thermal Processing and Shelf-Life Evaluation of Red-Bellied Pacu (Piaractus brachypomus) Fish Masala in Retort Pouches - Chavan, Sachin Dnyanoba; Bojayanaik, Manjanaik; Ganachari, Jyoti; Alakuntla, Preethi; Thimmappa, Ananya; Vaghabhai, Taral Pravinkumar; Baraiya, Kirankumar Gopalbhai; Naik, Sagar Naik Chandra; Dara, Pavan Kumar; Alandur, Veena Shetty (Fishery Technology, 2025)
A convenient and shelf-stable ready-to-eat fish masala dish was developed using red-bellied pacu (Piaractus brachypomus) in the present study. The work focused on optimizing thermal processing conditions and evaluating their impact on the product’s safety, sensory quality, and storage stability at ambient temperature. Flexible retortable pouches were used for packaging, and heat penetration was monitored using ELLAB thermal data. The fh values recorded were 14.5 and 13.5 min for F0 values of 6.0 and 7.0, with corresponding process times of 24.83 and 25.51 min and cook values of 59.67 and 60.90 min, respectively. Sensory, biochemical, and microbiological quality tests were carried out during storage. Heat processing caused only minimal changes in the fatty acid and amino acid profiles. No microbial growth was observed for up to 150 days. The product processed at an F0 value of 6.0 retained better overall quality during storage. The results highlight the potential of pacu as a promising raw material for the development of ethnic ready-to-eat fish dishes.